Photo-curable resin composition and cured product

A photo-curable resin composition with controlled swelling and modulus properties addresses adhesive strength issues in portable devices, maintaining high durability against sebum, sweat, and chemicals.

JP7765287B2Active Publication Date: 2025-11-06SEKISUI CHEMICAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021540860
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-29
Filing Date
2021-06-17
Publication Date
2025-11-06
Estimated Expiration
2041-06-17

AI Technical Summary

Technical Problem

Conventional light- and moisture-curing adhesives used in portable electronic devices such as smartphones and wearable devices suffer from a decrease in adhesive strength due to sebum, sweat, and chemicals, leading to peeling issues, and often have insufficient final adhesive strength.

Method used

A photo-curable moisture-curable resin composition containing specific ratios of a moisture-curable resin, a radical polymerizable compound, and a photopolymerization initiator, with a swelling ratio of 100% to 160% and a storage modulus of 1 MPa or more at 25% elongation, ensuring high adhesive strength even after prolonged contact with sebum, sweat, and chemicals.

Benefits of technology

The resin composition maintains excellent final adhesive strength and resistance to swelling, making it suitable for use in portable electronic devices by preventing peeling and ensuring durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007765287000004
    Figure 0007765287000004
  • Figure 0007765287000001
    Figure 0007765287000001
  • Figure 0007765287000002
    Figure 0007765287000002
Patent Text Reader

Abstract

This photo / moisture curable resin composition contains (A) a moisture curable resin, (B) a radically polymerizable compound and (C) a photopolymerization initiator; and a cured body of this photo / moisture curable resin composition has a swelling ratio of from 100% to 160% after being immersed in oleic acid at 65°C at a humidity of 90% RH for 72 hours, while having a storage elastic modulus of 1 MPa or more at 25% elongation.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a light-moisture-curable resin composition and a cured product of the light-moisture-curable resin composition. [Background technology]

[0002] Photo-moisture-curable resin compositions are known as adhesives with excellent flexibility and shape retention. Photo-moisture-curable resin compositions are widely used, for example, in semiconductor applications and electronic device applications. For example, Patent Document 1 discloses a photo-moisture-curable resin composition used in electronic device applications that contains a radical polymerizable compound, a moisture-curable urethane resin, and a photoradical polymerization initiator. Patent Document 1 discloses that the moisture-curable urethane resin used has a polyether skeleton obtained by reacting a polyol such as polyether polyol with a polyisocyanate. It is also known that polycarbonate polyol is used as a urethane raw material, as shown in Patent Document 2, for example. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2015 / 056717 [Patent Document 2] International Publication No. 2017 / 138337 Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, portable electronic devices such as mobile phones including smartphones and tablet personal computers have become widely used. Wearable devices are also becoming increasingly popular as portable electronic devices. Because portable electronic devices such as smartphones and wearable devices spend long periods of time in contact with the skin, the adhesives used in portable electronic devices often come into contact with sebum, sweat, and chemicals contained in skin care products such as cosmetics and sunscreen.

[0005] However, conventional light- and moisture-curing adhesives can have problems such as a decrease in adhesive strength due to sebum, sweat, chemicals, etc., which can cause problems such as peeling of the adherend. Furthermore, conventional light- and moisture-curing resin compositions sometimes have insufficient adhesive strength after light and moisture curing (also called "final adhesive strength").

[0006] Therefore, an object of the present invention is to provide a light- and moisture-curable resin composition that has excellent final adhesive strength after light and moisture curing, and maintains high adhesive strength even after prolonged contact with sebum, sweat, chemicals, etc., and that can be suitably used, for example, as an adhesive for portable electronic devices. [Means for solving the problem]

[0007] As a result of extensive research, the present inventors have found that the above-mentioned problems can be solved by reducing the swelling ratio of the cured product with oleic acid and increasing the storage modulus at 25% elongation in a photo-moisture-curable resin composition containing a radical polymerizable compound, a moisture-curable resin, and a photopolymerization initiator, and have completed the present invention as described below. The present invention provides the following [1] to

[19] . [1] A photo-curable moisture-curable resin composition containing a moisture-curable resin (A), a radical polymerizable compound (B), and a photopolymerization initiator (C), A photo-moisture-curable resin composition, wherein a swelling ratio after immersion of a cured product of the photo-moisture-curable resin composition in oleic acid at 65°C and a humidity of 90% RH for 72 hours is 100% or more and 160% or less, and the storage modulus of the cured product at 25% elongation is 1 MPa or more. [2] The photo-curable resin composition according to [1], wherein the moisture-curable resin (A) contains at least one selected from the group consisting of moisture-curable resins having a polycarbonate skeleton and moisture-curable resins having a polyester skeleton. [3] The photo-curable resin composition according to [2], wherein the content of at least one selected from the group consisting of moisture-curable resins having a polycarbonate skeleton and moisture-curable resins having a polyester skeleton is 30% by mass or more and 100% by mass or less based on the total amount of the moisture-curable resin (A). [4] The photo-curable moisture-curable resin composition according to any one of the above [1] to [3], wherein the moisture-curable resin (A) has an aromatic isocyanate group. [5] The photo-curable moisture-curable resin composition according to any one of the above [1] to [4], wherein the moisture-curable resin (A) is a moisture-curable urethane resin (a1). [6] The photo-curable moisture-curable resin composition according to any one of the above [1] to [5], wherein the content of the moisture-curable resin (A) is 15% by mass or more and 85% by mass or less. [7] The photo-curable resin composition according to any one of the above [1] to [6], wherein the radical polymerizable compound (B) contains at least one selected from the group consisting of a radical polymerizable compound having an aromatic ring and a radical polymerizable compound having an imide ring. [8] The photo-curable resin composition according to the above [7], wherein the content of at least one compound selected from the group consisting of the radical polymerizable compound having an aromatic ring and the radical polymerizable compound having an imide ring is 20% by mass or more and 100% by mass or less, based on the total amount of the radical polymerizable compound (B). [9] The photo-curable resin composition according to any one of the above [1] to [8], wherein the content of the radical polymerizable compound (B) is 14 mass % or more and 84 mass % or less based on the total amount of the photo-curable resin composition.

[10] The photo-curable moisture-curable resin composition according to any one of the above [1] to [9], wherein the mass ratio (B / A) of the radical polymerizable compound (B) to the moisture-curable resin (A) is 0.2 or more and 3 or less.

[11] The photo-curable resin composition according to any one of the above [1] to

[10] , wherein the photopolymerization initiator (C) is at least one selected from the group consisting of benzophenone compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin ether compounds, and thioxanthone.

[12] The photo-curable resin composition according to any one of the above [1] to

[11] , wherein the storage modulus at 25% elongation is 15 MPa or less.

[13] An adhesive for electronic components, comprising the photo- and moisture-curable resin composition according to any one of the above [1] to

[12] .

[14] An adhesive for portable electronic devices, comprising the light-curable moisture-curable resin composition according to any one of the above [1] to

[12] .

[15] A cured product of a photo-curable moisture-curable resin composition containing a moisture-curable resin, a radical polymerizable compound, and a photopolymerization initiator, A cured product having a swelling rate of 100% or more and 160% or less after immersion in oleic acid at 65°C and 90% RH for 72 hours, and a storage modulus of 1 MPa or more at 25% elongation.

[16] An electronic component comprising the cured product according to

[15] above and a substrate.

[17] A portable electronic device comprising the cured product according to

[15] above and a substrate.

[18] An electronic component comprising a cured product obtained by curing the light-curable moisture-curable resin composition according to any one of the above [1] to

[12] .

[19] A portable electronic device comprising a cured product obtained by curing the light-curable resin composition according to any one of [1] to

[12] above. [Effects of the Invention]

[0008] The photo- and moisture-curable resin composition of the present invention has excellent final adhesive strength after photo- and moisture-curing, and maintains high adhesive strength even after prolonged contact with sebum, sweat, chemicals, etc., and can be suitably used, for example, as an adhesive for portable electronic devices. [Brief explanation of the drawings]

[0009] [Figure 1] 1A and 1B are schematic diagrams showing an adhesiveness test method, in which FIG. 1A is a plan view and FIG. 1B is a side view. DETAILED DESCRIPTION OF THE INVENTION

[0010] <Curable resin composition> The photo-moisture-curable resin composition of the present invention is a photo-moisture-curable resin composition containing a moisture-curable resin (A), a radically polymerizable compound (B), and a photopolymerization initiator (C). The photo-moisture-curable resin composition of the present invention has a swelling ratio (also referred to as "oleic acid swelling ratio") of 100% to 160% after immersion of a cured product in oleic acid at 65°C and 90% RH for 72 hours, and the cured product has a storage modulus of 1 MPa or more at 25% elongation. The light-and-moisture-curable resin composition of the present invention has the above-described configuration, and has excellent final adhesive strength after light and moisture curing, and the final adhesive strength is maintained at a high value even after the cured product has been in contact with sebum, sweat, chemicals, etc. for a long period of time. Therefore, the composition can be suitably used as an adhesive for portable electronic devices such as smartphones and wearable devices.

[0011] [Oleic acid swelling rate] As described above, the photo-moisture-curable resin composition of the present invention has an oleic acid swelling ratio of 100% or more and 160% or less in the cured product. If the swelling ratio exceeds 160%, for example, when used for a long period of time in a portable electronic device, sebum, sweat, chemicals, etc. accumulate in the cured product, causing the cured product to swell, thereby reducing the amount of resin per unit volume and further reducing the anchoring effect of the cured product on the adherend. As a result, the adhesive strength to the adherend decreases with use, making the adherend more susceptible to problems such as peeling, making it difficult to use the composition as an adhesive for portable electronic devices such as smartphones.

[0012] From the viewpoint of maintaining a high adhesive strength even after long-term use in portable electronic devices and the like, the oleic acid swelling ratio is preferably 140% or less, more preferably 130% or less, and even more preferably 117% or less.

[0013] The swelling ratio with oleic acid can be determined by measuring the ratio of the area of ​​the film-like cured product after swelling with oleic acid to the area before swelling with oleic acid. The oleic acid swelling ratio can be adjusted by appropriately changing the types and amounts of the moisture-curable resin (A) and the radically polymerizable compound (B), for example. Oleic acid has similar physical properties to sebum components and ingredients found in cosmetics and skin care products, and has a high swelling rate with resins. Therefore, the oleic acid swelling evaluation test is suitable as an accelerated degradation model test for electronic devices that are used in contact with the skin for long periods of time.

[0014] [Storage modulus at 25% elongation] The photo- and moisture-curable resin composition of the present invention has a storage modulus of 1 MPa or more at 25% elongation of the cured product. If the storage modulus of the cured product at 25% elongation is lower than 1 MPa, the adhesive strength (final adhesive strength) after light and moisture curing is likely to be insufficient. Furthermore, the cured product is likely to swell due to oil, and the adhesive strength is likely to decrease when it comes into contact with sebum, sweat, chemicals, etc. From the viewpoint of improving the final adhesive strength and maintaining good adhesive strength even after contact with sebum, sweat, chemicals, etc., the storage modulus at 25% elongation is preferably 1.5 MPa or more, and more preferably 2.0 MPa or more. Furthermore, the storage modulus at 25% elongation is not particularly limited, but from the viewpoint of improving the flexibility of the cured product, it is preferably 15 MPa or less, and more preferably 10 MPa or less.

[0015] The storage modulus at 25% elongation is the storage modulus measured at 25° C. when the cured product is elongated by 25%. Details of the method for measuring the storage modulus are as shown in the examples below. The storage modulus of the cured product at 25% elongation can be adjusted by appropriately selecting, for example, the types and amounts of the moisture-curable resin (A) and the radically polymerizable compound (B).

[0016] The above-mentioned oleic acid swelling ratio and storage modulus at 25% elongation can be determined by preparing a cured sample of the curable resin composition of the present invention and measuring the storage modulus at 25% elongation and the oleic acid swelling ratio of the cured sample. The cured sample can be prepared by curing the curable resin composition under conditions that allow it to be sufficiently cured, and specifically, the cured sample can be prepared by curing the curable resin composition under the following conditions. That is, the photo-curable resin composition was exposed to ultraviolet light at 1000 mJ / cm using a UV-LED (wavelength 365 nm). 2 The composition is then exposed to light for light curing, and then allowed to stand at 25°C and 50% RH for 24 hours for moisture curing to obtain a cured sample.

[0017] [Adhesive strength] The photo- and moisture-curable resin composition of the present invention has an adhesive strength (final adhesive strength) of 70 N / 25 mm after photo- and moisture-curing. 2 It is preferable that it is 150N / 25mm or more. 2 The light-curable resin composition preferably has a final adhesive strength of 70 N / 25 mm or more. 2 With the above, adherends can be joined with high adhesive strength by temporary bonding through photocuring followed by main bonding through moisture curing.

[0018] The photo-moisture-curable resin composition of the present invention preferably has an adhesive strength retention rate, expressed as the ratio of the final adhesive strength after immersion in oleic acid to the final adhesive strength (the final adhesive strength before immersion in oleic acid), of 10% or more. When the cured product of the photo-moisture-curable resin composition has an adhesive strength retention rate of 10% or more, it can sufficiently maintain high adhesive strength even when used for a long period of time in portable electronic devices and the like, and the cured product comes into contact with a certain amount of sebum, sweat, chemicals, etc. From this perspective, an adhesive strength retention rate of 30% or more is more preferable, and 50% or more is even more preferable. The adhesive strength retention rate is preferably closer to 100% from the viewpoint of maintaining high final adhesive strength even when exposed to a large amount of sebum, sweat, chemicals, etc., and is not particularly limited as long as it is 100% or less.

[0019] In measuring the final adhesive strength before and after immersion in oleic acid, an adhesion test sample is first prepared by bonding a glass plate and a polycarbonate plate via a photo-cured and moisture-cured photo- and moisture-cured resin composition. The prepared adhesion test sample was then left to stand for a further 72 hours at 25°C and 50% RH, after which it was pulled in the shear direction and the strength at which the glass plate and the polycarbonate plate peeled apart was measured, and this strength was taken as the final adhesive strength before immersion in oleic acid. The prepared adhesion test sample was then immersed in oleic acid at 65°C and 90% RH for 72 hours, and the immersed adhesion test sample was then pulled in the shear direction to measure the strength at which the glass plate and polycarbonate plate peeled apart. This strength was taken as the final adhesive strength after immersion in oleic acid. The details of the method for preparing the sample for the adhesiveness test and the method for measuring the adhesive strength are as described in the Examples.

[0020] (Moisture-curing resin (A)) The photo-moisture-curable resin composition of the present invention contains a moisture-curable resin (A). In the present invention, the inclusion of the moisture-curable resin (A) imparts moisture-curability in addition to photo-curability to the resin composition, which makes it easier to increase the final adhesive strength. Specific examples of the moisture-curable resin (A) include isocyanate group-containing resins and hydrolyzable silyl group-containing resins. Isocyanate group-containing resins cure when the isocyanate group in the molecule reacts with water present in the air or on the adherend. Hydrolyzable silyl group-containing resins cure when the hydrolyzable silyl group in the molecule reacts with water present in the air or on the adherend. Of the above-mentioned moisture-curable resins (A), isocyanate group-containing resins are preferred. The moisture-curable resin (A) may be used alone or in combination of two or more kinds.

[0021] The moisture-curable resin is preferably a moisture-curable urethane resin (a1). The moisture-curable urethane resin (a1) may be the above-mentioned isocyanate group-containing resin, and is preferably a resin having an isocyanate group and a urethane bond.

[0022] The isocyanate group-containing resin is not particularly limited in terms of the isocyanate group it contains, and may be either an aromatic isocyanate group or an aliphatic isocyanate group, with aromatic isocyanate groups being preferred. Therefore, it is more preferred that the moisture-curable resin (A) contains a moisture-curable urethane resin (a1) having an aromatic isocyanate group. The aromatic isocyanate group is an isocyanate group directly bonded to an aromatic ring, and the aliphatic isocyanate group is an isocyanate group directly bonded to an aliphatic carbon atom.

[0023] When the moisture-curable resin (A) contains an aromatic isocyanate group, the storage modulus at 25% elongation increases, making it easier to improve the final adhesive strength. Furthermore, the oil resistance of the cured product of the photo-moisture-curable resin composition improves, making it easier to maintain a high final adhesive strength even after contact with oil. The moisture-curable resin (A) may be a combination of a resin having an aromatic isocyanate group and a resin having an aliphatic isocyanate group, or the moisture-curable resin (A) may be a compound having both an aromatic isocyanate group and an aliphatic isocyanate group in one molecule. The aromatic isocyanate group is an isocyanate group derived from an aromatic isocyanate compound, the details of which are described later. The aliphatic isocyanate group is an isocyanate group derived from an aliphatic isocyanate compound, the details of which are described later.

[0024] The moisture-curable resin (A) preferably contains at least one selected from moisture-curable resins having a polycarbonate skeleton and moisture-curable resins having a polyester skeleton. By including these moisture-curable resins in the photo-moisture-curable resin composition, the storage modulus of the cured product at 25% elongation can be easily increased, and the final adhesive strength can be easily improved. Furthermore, the oil resistance can be easily improved, and the adhesive strength after immersion in oleic acid can be easily maintained at a high value. Among these, the moisture-curable resin (A) more preferably contains a moisture-curable resin having a polycarbonate skeleton, from the viewpoint of making it easier to increase the storage modulus of the cured product at 25% elongation.

[0025] The moisture-curing resin having a polycarbonate skeleton and the moisture-curing resin having a polyester skeleton are preferably moisture-curing urethane resins (a1), and among them, moisture-curing urethane resins (a1) having an isocyanate group are more preferred. These moisture-curing urethane resins (a1) having an isocyanate group may have at least either an aliphatic isocyanate group or an aromatic isocyanate group, but preferably have an aromatic isocyanate group. Therefore, it is particularly preferred that the moisture-curing resin (A) contains a moisture-curing urethane resin (a1) having a polycarbonate skeleton and an aromatic isocyanate group.

[0026] (Moisture-curing urethane resin (a1)) Hereinafter, the case where the moisture-curing resin (A) is a moisture-curing urethane resin (a1) will be described in more detail. As described above, the moisture-curing urethane resin (a1) preferably has an isocyanate group in addition to a urethane bond. The moisture-curing urethane resin (a1) may have only one isocyanate group per molecule, or may have two or more isocyanate groups per molecule, but it is more preferable that the moisture-curing urethane resin (a1) has isocyanate groups at both ends of the main chain of the molecule.

[0027] The moisture-curable urethane resin (a1) can be obtained by reacting a polyol compound having two or more hydroxyl groups in one molecule with a polyisocyanate compound having two or more isocyanate groups in one molecule. The reaction between the polyol compound and the polyisocyanate compound is usually carried out in a molar ratio of hydroxyl groups (OH) in the polyol compound to isocyanate groups (NCO) in the polyisocyanate compound, [NCO] / [OH], within the range of 2.0 to 2.5.

[0028] In the present invention, a polycarbonate polyol is used as the polyol compound that serves as the raw material of the moisture-curable urethane resin (a1), thereby introducing a polycarbonate skeleton into the moisture-curable urethane resin (a1), thereby producing a moisture-curable urethane resin (a1) having a polycarbonate skeleton. The polycarbonate polyol is preferably a polycarbonate diol, and specific examples of the polycarbonate diol include compounds represented by the following formula (1).

[0029] [ka] In formula (1), R is a divalent hydrocarbon group having 4 to 16 carbon atoms, and n is an integer of 2 to 500.

[0030] In formula (1), R is preferably an aliphatic saturated hydrocarbon group. When R is an aliphatic saturated hydrocarbon group, heat resistance and flexibility tend to be improved. Furthermore, yellowing due to thermal degradation and the like is less likely to occur, and weather resistance is also improved. R consisting of an aliphatic saturated hydrocarbon group may have a chain structure or a cyclic structure, but preferably has a chain structure. Furthermore, R having a chain structure may be either linear or branched. n is preferably 5-200, more preferably 10-150, and even more preferably 20-50. Furthermore, the R contained in the polycarbonate polyol constituting the moisture-curable urethane resin (a1) may be used alone or in combination of two or more. When two or more types are used in combination, it is preferable that at least a portion is a linear aliphatic saturated hydrocarbon group having 6 or more carbon atoms. Furthermore, it is preferable that one molecule contains two or more types of R, and more preferably one molecule contains two or three types of R. The chain aliphatic saturated hydrocarbon group having 6 or more carbon atoms preferably has 6 to 12 carbon atoms, more preferably 6 to 10 carbon atoms, and even more preferably 6 to 8 carbon atoms. Specific examples of R include linear groups such as tetramethylene, pentylene, hexamethylene, heptamethylene, octamethylene, nonamethylene, and decamethylene, and branched groups such as methylpentylene groups (e.g., 3-methylpentylene) and methyloctamethylene groups. Multiple R groups in one molecule may be the same or different. Furthermore, from the viewpoint of achieving a certain elastic modulus or higher, R preferably contains a branched saturated aliphatic hydrocarbon group, and from the viewpoint of weather resistance, R preferably contains a linear saturated aliphatic hydrocarbon group. Branched and linear R groups may be used in combination in the polycarbonate polyol. The polycarbonate polyols may be used singly or in combination of two or more.

[0031] In the present invention, a polyester polyol is used as the polyol compound serving as a raw material for the moisture-curable urethane resin (a1), thereby introducing a polyester skeleton into the moisture-curable urethane resin (a1), thereby forming a moisture-curable urethane resin (a1) having a polyester skeleton. Examples of the polyester polyol include polyester polyol obtained by reacting a polycarboxylic acid with a polyol, and poly-ε-caprolactone polyol obtained by ring-opening polymerization of ε-caprolactone.

[0032] Examples of the polycarboxylic acids used as raw materials for polyester polyols include divalent aromatic carboxylic acids such as terephthalic acid, isophthalic acid, 1,5-naphthalic acid, and 2,6-naphthalic acid, divalent aliphatic carboxylic acids such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decamethylene dicarboxylic acid, and dodecamethylene dicarboxylic acid, trivalent or higher aromatic carboxylic acids such as trimellitic acid, trimesic acid, pyromellitic acid, and naphthalene tricarboxylic acid, and trivalent or higher aliphatic carboxylic acids such as cyclohexane tricarboxylic acid and hexane tricarboxylic acid. These polycarboxylic acids may be used alone or in combination of two or more. Examples of polyols that can be used as raw materials for polyester polyols include ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol, cyclohexanediol, etc. These polyols may be used alone or in combination of two or more.

[0033] In addition, the moisture-curing urethane resin (a1) may contain both a polycarbonate skeleton and a polyester skeleton by using both a polycarbonate polyol and a polyester polyol as the polyol compound that serves as the raw material for the moisture-curing urethane resin (a1). In other words, the moisture-curing urethane resin (a1) may be a moisture-curing urethane resin (a1) having both a polycarbonate skeleton and a polyester skeleton in one molecule. In this specification, the term "moisture-curing urethane resin (a1) having a polycarbonate skeleton" or "moisture-curing resin having a polycarbonate skeleton" also includes a moisture-curing urethane resin (a1) or a moisture-curing resin that contains both a polycarbonate skeleton and a polyester skeleton.

[0034] Examples of polyisocyanate compounds that can be used as raw materials for the moisture-curable urethane resin (a1) include aromatic polyisocyanate compounds and aliphatic polyisocyanate compounds. Examples of aromatic polyisocyanate compounds include diphenylmethane diisocyanate, liquid modified diphenylmethane diisocyanate, tolylene diisocyanate, naphthalene-1,5-diisocyanate, etc. The aromatic polyisocyanate compound may be a polymerized product of these compounds, or may be polymeric MDI, etc. Examples of aliphatic polyisocyanate compounds include hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine diisocyanate, norbornane diisocyanate, transcyclohexane-1,4-diisocyanate, isophorone diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated diphenylmethane diisocyanate, cyclohexane diisocyanate, bis(isocyanatomethyl)cyclohexane, dicyclohexylmethane diisocyanate, etc. The aliphatic polyisocyanate compound may be a polymerized version of these compounds. The polyisocyanate compounds may be used alone or in combination of two or more kinds. In the present invention, when an aromatic polyisocyanate compound is used in the synthesis of the moisture-curable urethane resin (a1), the moisture-curable urethane resin (a1) contains an aromatic isocyanate group, and when an aliphatic polyisocyanate compound is used, the moisture-curable urethane resin (a1) contains an aliphatic isocyanate group.

[0035] The moisture-curable resin (A) may consist of at least one selected from moisture-curable resins having a polycarbonate skeleton and moisture-curable resins having a polyester skeleton, but may also contain moisture-curable resins other than these (also referred to as "other moisture-curable resins"). In the photo-curable resin composition, the content of at least one selected from a moisture-curing resin having a polycarbonate skeleton and a moisture-curing resin having a polyester skeleton is preferably 30% by mass or more, more preferably 50% by mass or more, even more preferably 70% by mass or more, and even more preferably 80% by mass or more, based on the total amount of moisture-curing resin (A). Increasing the content of these moisture-curing resins (A) increases the storage modulus at 25% elongation and also improves oil resistance. This makes it easier to improve the final adhesive strength of the cured product and maintain a high adhesive strength even after contact with oil. Therefore, the higher the content of these moisture-curing resins, the better, and it is sufficient to set the content to 100% by mass or less, based on the total amount of moisture-curing resin (A).

[0036] The other moisture-curing resin is not particularly limited, but may be a moisture-curing resin having a polyether skeleton. The moisture-curing resin having a polyether skeleton is preferably a moisture-curing urethane resin (a1), more preferably a moisture-curing urethane resin (a1) having an isocyanate group. The moisture-curing urethane resin (a1) may have either an aromatic isocyanate group or an aliphatic isocyanate group, but preferably has an aromatic isocyanate group. Using a moisture-curing resin having a polyether skeleton as the other moisture-curing resin makes it easier to improve the final adhesive strength.

[0037] The moisture-curable urethane resin having a polyether skeleton is obtained by introducing a polyether skeleton into the urethane resin by using a polyether polyol as the polyol compound. The urethane resin having a polyether skeleton can be obtained by reacting a polyether polyol having two or more hydroxyl groups per molecule with a polyisocyanate compound having two or more isocyanate groups per molecule.

[0038] Examples of polyether polyols include polyethylene glycol, polypropylene glycol, ring-opening polymers of tetrahydrofuran, ring-opening polymers of 3-methyltetrahydrofuran, random copolymers or block copolymers of these or their derivatives, bisphenol-type polyoxyalkylene modified products, etc. Among these, polypropylene glycol or ring-opening polymers of 3-methyltetrahydrofuran are preferred from the viewpoint of easily improving the coatability of the photo-curable resin composition. Here, the bisphenol-type polyoxyalkylene modified product is a polyether polyol obtained by addition reaction of an alkylene oxide (e.g., ethylene oxide, propylene oxide, butylene oxide, isobutylene oxide, etc.) with the active hydrogen moiety of a bisphenol-type molecular skeleton. The polyether polyol may be a random copolymer or a block copolymer. The bisphenol-type polyoxyalkylene modified product preferably has one or more alkylene oxides added to both ends of the bisphenol-type molecular skeleton. The bisphenol type is not particularly limited, and examples thereof include A-type, F-type, S-type, etc., with bisphenol A-type being preferred. As the polyisocyanate compound, the above-mentioned polyisocyanate compounds can be used.

[0039] The moisture-curable urethane resin having a polyether skeleton preferably further includes one obtained using a polyol compound having a structure represented by the following formula (2): By using a polyol compound having a structure represented by the following formula (2), it is possible to obtain a photo-moisture-curable resin composition having excellent adhesive properties and a cured product that is flexible and has good elongation, and which has excellent compatibility with the radically polymerizable compound (B). Among these, polyether polyols made from polypropylene glycol, ring-opening polymerized compounds of tetrahydrofuran (THF) compounds, or ring-opening polymerized compounds of tetrahydrofuran compounds having a substituent such as a methyl group are preferred, and polypropylene glycol is more preferred.

[0040] [ka] In formula (2), R represents a hydrogen atom, a methyl group, or an ethyl group, l is an integer of 0 to 5, m is an integer of 1 to 500, and n is an integer of 1 to 10. l is preferably an integer of 0 to 4, m is preferably an integer of 50 to 200, and n is preferably an integer of 1 to 5. When l is 0, this means that the carbon bonded to R is directly bonded to oxygen. Among the above, the sum of n and l is more preferably 1 or more, and further preferably 1 to 3. Furthermore, R is more preferably a hydrogen atom or a methyl group, and particularly preferably a methyl group.

[0041] The weight-average molecular weight of the moisture-curable resin (A) is not particularly limited, but a preferred lower limit is 800 and a preferred upper limit is 20,000. When the weight-average molecular weight is 800 or more, the crosslink density does not become too high during curing, and flexibility after curing tends to be high. Furthermore, in a semi-cured state after photocuring but before moisture curing, the composition has a certain level of hardness or more, making it easier to ensure excellent shape retention. Furthermore, when the shape retention is excellent, a photo-moisture-curable resin composition applied, for example, with a dispenser, can maintain a certain height after photocuring, and the cured product of the photo-moisture-curable resin composition can ensure a certain distance between adherends. Furthermore, by making the weight average molecular weight 20,000 or less, the photo- and moisture-curable resin composition has appropriate fluidity even at room temperature (for example, 25°C) before being cured with light and moisture, and has good room temperature applicability.

[0042] The weight-average molecular weight of the moisture-curable resin (A) is more preferably 1500 at its lower limit, 12000 at its upper limit, 2000 at its lower limit, and 8000 at its upper limit. The weight-average molecular weight in this specification is a value determined by gel permeation chromatography (GPC) and converted into polystyrene equivalents. An example of a column used for measuring the weight-average molecular weight converted into polystyrene equivalents by GPC is Shodex LF-804 (manufactured by Showa Denko K.K.). An example of a solvent used in GPC is tetrahydrofuran.

[0043] The content of the moisture-curable resin (A) is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more, based on the total amount of the photo-moisture-curable resin composition. By making the content equal to or greater than these lower limits, the moisture curability of the photo-moisture-curable resin composition can be improved. In addition, oil resistance can be imparted to the cured product of the curable resin composition, and shape retention in a semi-cured state after photo-curing but before moisture curing can be improved. In addition, the storage modulus at 25% elongation can also be easily increased. The content of the moisture-curable resin (A) is preferably 85 mass % or less, more preferably 80 mass % or less, and even more preferably 75 mass % or less, based on the total amount of the photo-moisture-curable resin composition. By setting the content of the moisture-curable resin (A) to these upper limits or less, it becomes possible to contain a considerable amount of the radically polymerizable compound (B).

[0044] (Radical polymerizable compound (B)) The photo-moisture-curable resin composition of the present invention contains a radically polymerizable compound (B). The photo-moisture-curable resin composition is imparted with photo-curability by containing the radically polymerizable compound (B). The photo-moisture-curable resin composition has photo-curability, and thus a certain level of adhesive strength can be imparted to the composition simply by irradiating it with light, ensuring appropriate initial adhesive strength. Furthermore, by using the radically polymerizable compound (B) in addition to the moisture-curable resin (A), the photo-moisture-curable resin composition can easily ensure appropriate fluidity even at room temperature (e.g., 25°C) before light and moisture curing, thereby achieving good room-temperature applicability. The radical polymerizable compound (B) may have a radical polymerizable functional group in the molecule. The radical polymerizable functional group is preferably a compound having an unsaturated double bond, such as a (meth)acryloyl group, a vinyl group, a styryl group, or an allyl group.

[0045] Among the above, a (meth)acryloyl group is preferred from the viewpoint of adhesiveness, that is, the radical polymerizable compound (B) preferably contains a compound having a (meth)acryloyl group. Note that a compound having a (meth)acryloyl group will also be referred to as a "(meth)acrylic compound" hereinafter. Furthermore, in this specification, "(meth)acryloyl group" means an acryloyl group or a (meth)acryloyl group, "(meth)acrylic" means acrylic or methacrylic, and the same applies to other similar terms.

[0046] The radical polymerizable compound (B) preferably contains at least one selected from a radical polymerizable compound having an aromatic ring and a radical polymerizable compound having an imide ring. These compounds are preferably monofunctional compounds having one radical polymerizable functional group in the molecule, but may also be polyfunctional compounds having two or more radical polymerizable functional groups.

[0047] Examples of radically polymerizable compounds having an aromatic ring include monofunctional (meth)acrylic acid ester compounds having an aromatic ring. Specific examples include phenyl alkyl (meth)acrylates such as benzyl (meth)acrylate and 2-phenylethyl (meth)acrylate, and phenoxy alkyl (meth)acrylates such as phenoxyethyl (meth)acrylate. Furthermore, (meth)acrylates having multiple benzene rings such as a fluorene skeleton or a biphenyl skeleton may also be used, and specific examples include fluorene type (meth)acrylates and ethoxylated o-phenylphenol acrylate. Other examples include phenoxypolyoxyethylene (meth)acrylates such as phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenoxydiethylene glycol (meth)acrylate, and nonylphenoxypolyethylene glycol (meth)acrylate. Of these, phenoxyalkyl (meth)acrylates are preferred, and among these, phenoxyethyl (meth)acrylate is more preferred. Examples of radically polymerizable compounds having an imide ring include (meth)acrylic acid ester compounds having an imide ring such as N-(meth)acryloyloxyethylhexahydrophthalimide, and vinyl compounds having an imide ring such as N-vinylphthalimide, N-allylphthalimide, N-(3-butene-1-yne)phthalimide, and N-allyloxyphthalimide.

[0048] By including at least one compound selected from the group consisting of a radical polymerizable compound having an aromatic ring and a radical polymerizable compound having an imide ring, the photo- and moisture-curable resin composition improves oil resistance and prevents an increase in the swelling ratio with oleic acid. Furthermore, the storage modulus at 25% elongation of the cured product after photo- and moisture-curing is increased, making it easier to improve the final adhesive strength. Furthermore, in the semi-cured state after photo-curing and before moisture-curing, it is easier to increase the hardness and ensure excellent shape retention. The radical polymerizable compound (B) preferably contains either a radical polymerizable compound having an aromatic ring or a radical polymerizable compound having an imide ring, but may contain both.Moreover, the radical polymerizable compound (B) more preferably contains at least a radical polymerizable compound having an imide ring.

[0049] The radical polymerizable compound (B) may consist of at least one selected from a radical polymerizable compound having an aromatic ring and a radical polymerizable compound having an imide ring, but may also contain a radical polymerizable compound other than these (referred to as "other radical polymerizable compounds"). In the photo-moisture-curable resin composition, the content of at least one compound selected from a radical polymerizable compound having an aromatic ring and a radical polymerizable compound having an imide ring is preferably 20% by mass or more, more preferably 30% by mass or more, even more preferably 50% by mass or more, and even more preferably 80% by mass or more, based on the total amount of the radical polymerizable compound (B). The content of these compounds may be 100% by mass or less. Increasing the content of these compounds improves the oil resistance of the photo-moisture-curable resin composition and makes it easier to suppress the oleic acid swelling ratio. Furthermore, the storage modulus at 25% elongation of the cured product increases, making it easier to improve the final adhesive strength. Furthermore, shape retention and other properties are also easily improved.

[0050] Examples of other radical polymerizable compounds include various aliphatic (meth)acrylic compounds, and preferably, aliphatic urethane (meth)acrylates are used. The aliphatic urethane (meth)acrylates do not have residual isocyanate groups. The other radical polymerizable compounds may be monofunctional or polyfunctional, such as bifunctional, but are preferably monofunctional.

[0051] The aliphatic urethane (meth)acrylate is preferably monofunctional as described above, and for example, a compound obtained by reacting an isocyanate compound with a (meth)acrylic acid derivative having a hydroxyl group can be used. Examples of the (meth)acrylic acid derivative having a hydroxyl group include mono(meth)acrylates of dihydric alcohols such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, and polyethylene glycol, and mono(meth)acrylates of trihydric alcohols such as trimethylolethane, trimethylolpropane, and glycerin.

[0052] Examples of the isocyanate compound used to obtain the aliphatic urethane (meth)acrylate include aliphatic monoisocyanates such as butane isocyanate, hexane isocyanate, octane isocyanate, and decane isocyanate, and other alkane monoisocyanates (the number of carbon atoms in the alkane is preferably about 3 to 12), and cycloaliphatic monoisocyanates such as cyclopentane isocyanate, cyclohexane isocyanate, and isophorone monoisocyanate. More specifically, the monofunctional aliphatic urethane (meth)acrylate is preferably a urethane (meth)acrylate obtained by reacting the above-mentioned monoisocyanate compound with a mono(meth)acrylate of a dihydric alcohol, and a suitable specific example thereof is 1,2-ethanediol 1-acrylate 2-(N-alkylcarbamate) such as 1,2-ethanediol 1-acrylate 2-(N-butylcarbamate).

[0053] As the other radical polymerizable compound, compounds other than urethane (meth)acrylates can be used, for example, (meth)acrylic acid ester compounds other than those mentioned above can be used. The (meth)acrylic acid ester compound may be monofunctional or polyfunctional, but is preferably monofunctional.

[0054] Examples of monofunctional (meth)acrylic acid ester compounds include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, and lauryl (meth)acrylate. alkyl (meth)acrylates such as methyl (meth)acrylate, isomyristyl (meth)acrylate, and stearyl (meth)acrylate; (meth)acrylates having an alicyclic structure such as cyclohexyl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentenyl (meth)acrylate; 2-hydroxyethyl (meth)acrylate hydroxyalkyl (meth)acrylates such as 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; alkoxyalkyl (meth)acrylates such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, and 2-butoxyethyl (meth)acrylate; alkoxyethylene glycol (meth)acrylates such as methoxyethylene glycol (meth)acrylate and ethoxyethylene glycol (meth)acrylate; and polyoxyethylene (meth)acrylates such as methoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, ethoxytriethylene glycol (meth)acrylate, and ethoxypolyethylene glycol (meth)acrylate.

[0055] Further, examples of the monofunctional (meth)acrylic acid ester compound include (meth)acrylates having a heterocyclic structure such as tetrahydrofurfuryl (meth)acrylate, alkoxylated tetrahydrofurfuryl (meth)acrylate, cyclic trimethylolpropane formal (meth)acrylate, 3-ethyl-3-oxetanylmethyl (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-octafluoropentyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, glycidyl (meth)acrylate, and 2-(meth)acryloyloxyethyl phosphate.

[0056] Examples of bifunctional (meth)acrylic acid ester compounds include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 2-n-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, ) acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, dimethyloldicyclopentadienyl di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide-modified isocyanuric acid di(meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate, carbonate diol di(meth)acrylate, polyether diol di(meth)acrylate, polyester diol di(meth)acrylate, polycaprolactone diol di(meth)acrylate, polybutadiene diol di(meth)acrylate, and the like.

[0057] Furthermore, examples of the (meth)acrylic acid ester compounds having three or more functional groups include trimethylolpropane tri(meth)acrylate, ethylene oxide-added trimethylolpropane tri(meth)acrylate, propylene oxide-added trimethylolpropane tri(meth)acrylate, caprolactone-modified trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ethylene oxide-added isocyanuric acid tri(meth)acrylate, glycerin tri(meth)acrylate, propylene oxide-added glycerin tri(meth)acrylate, tris(meth)acryloyloxyethyl phosphate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.

[0058] As the other radical polymerizable compound, other radical polymerizable compounds other than those mentioned above can also be used as appropriate. Examples of other radical polymerizable compounds include (meth)acrylamide compounds such as N,N-dimethyl(meth)acrylamide, N-(meth)acryloylmorpholine, N-hydroxyethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and N,N-dimethylaminopropyl(meth)acrylamide, and vinyl compounds such as N-vinyl-2-pyrrolidone and N-vinyl-ε-caprolactam. Epoxy(meth)acrylates can also be used.

[0059] The content of the radical polymerizable compound (B) is preferably 14% by mass or more, more preferably 19% by mass or more, and even more preferably 24% by mass or more, based on the total amount of the photo-moisture-curable resin composition. By making the content equal to or greater than these lower limits, it becomes easier to impart appropriate photo-curability to the photo-moisture-curable resin composition. In addition, the flexibility of the cured product becomes good, and it also becomes easier to impart room temperature applicability to the photo-moisture-curable resin composition. Furthermore, the content of the radical polymerizable compound (B) is preferably 84 mass % or less, more preferably 79 mass % or less, and even more preferably 74 mass % or less, based on the total amount of the photo-moisture-curable resin composition. By setting the content of the radical polymerizable compound (B) to these upper limits or less, the photo-moisture-curable resin composition becomes more likely to contain an appropriate amount of the moisture-curable resin (A), making it easier to improve oil resistance, adhesion, etc.

[0060] In the photo-moisture-curable resin composition, the mass ratio (B / A) of the radically polymerizable compound (B) to the moisture-curable urethane resin (A) is preferably 0.2 to 3, more preferably 0.3 to 2, even more preferably 0.5 to 1.5, and even more preferably 0.6 to 1.3. By having the mass ratio within these ranges, the photo-moisture-curable resin composition can be imparted with a good balance of photocurability and moisture curability, and both the initial adhesive strength after photocuring and the adhesive strength after photocuring and moisture curing (final adhesive strength) can be improved. Furthermore, it also becomes easier to impart appropriate oil resistance, making it easier for the cured product to maintain a high adhesive strength even after prolonged contact with sebum, sweat, chemicals, and the like.

[0061] (Photopolymerization initiator (C)) The light-moisture-curable resin composition of the present invention further contains a photopolymerization initiator (C). By containing a photopolymerization initiator, it is possible to appropriately impart photocurability to the light-moisture-curable resin composition. Examples of the photopolymerization initiator include benzophenone compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin ether compounds, and thioxanthone. Among the above photopolymerization initiators, commercially available ones include, for example, IRGACURE184, IRGACURE369, IRGACURE379, IRGACURE651, IRGACURE784, IRGACURE819, IRGACURE907, IRGACURE2959, IRGACURE OXE01, Lucirin TPO (all manufactured by BASF), benzoin methyl ether, benzoin ethyl ether, and benzoin isopropyl ether (all manufactured by Tokyo Chemical Industry Co., Ltd.).

[0062] The content of the photopolymerization initiator (C) in the photo-moisture-curable resin composition is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 7 parts by mass, and even more preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the radically polymerizable compound (B). When the content of the photopolymerization initiator (C) is within these ranges, the resulting photo-moisture-curable resin composition has excellent photocurability and storage stability. Furthermore, by ensuring the content within the above ranges, the photo-radical polymerizable compound is appropriately cured, making it easier to achieve good adhesive strength.

[0063] (Moisture cure catalyst) The curable resin composition preferably contains a moisture-cure-accelerating catalyst that accelerates the moisture-cure reaction of the moisture-curable resin. By using the moisture-cure-accelerating catalyst, the curable resin composition has better moisture curability and is more likely to have increased adhesive strength. Specific examples of moisture-cure-accelerating catalysts include amine compounds, metal catalysts, etc. Examples of amine compounds include compounds having a morpholine skeleton such as di(methylmorpholino)diethyl ether, 4-morpholinopropylmorpholine, and 2,2'-dimorpholinodiethyl ether, dimethylamino group-containing amine compounds having two dimethylamino groups such as bis(2-dimethylaminoethyl)ether and 1,2-bis(dimethylamino)ethane, triethylamine, 1,4-diazabicyclo[2.2.2]octane, and 2,6,7-trimethyl-1,4-diazabicyclo[2.2.2]octane. Examples of metal catalysts include tin compounds such as di-n-butyltin dilaurate, di-n-butyltin diacetate, and tin octoate; zinc compounds such as zinc octoate and zinc naphthenate; and other metal compounds such as zirconium tetraacetylacetonate, copper naphthenate, and cobalt naphthenate.

[0064] (coupling agent) The photo-curable resin composition may contain a coupling agent. By including a coupling agent in the photo-curable resin composition, adhesive strength can be easily improved. Examples of coupling agents include silane coupling agents, titanate coupling agents, and zirconate coupling agents. Among these, silane coupling agents are preferred because of their excellent effect of improving adhesiveness.

[0065] Examples of silane coupling agents include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 3-(meth)acryloyloxypropyltrimethoxysilane, 3-(meth)acryloyloxypropyltriethoxysilane, 3-(meth)acryloyloxypropylmethyldimethoxysilane, 3-(meth)acryloyloxypropylmethyldiethoxysilane, vinyltrimetho Examples of suitable silanes include dimethylsilane, vinyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropylmethyldimethoxysilane, 3-isocyanatepropyltriethoxysilane, 3-isocyanatepropylmethyldiethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldiethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, tedyltrimethoxysilane, and 1,6-bis(trimethoxysilyl)hexane.

[0066] Examples of the titanate coupling agent include titanium diisopropoxybis(acetylacetonate), titanium tetraacetylacetonate, and titanium diisopropoxybis(ethylacetoacetate). Examples of the zirconate coupling agent include zirconium tetra-normal propoxide and zirconium tetra-normal butoxide. The coupling agent is preferably a silane coupling agent, and among the silane coupling agents, an isocyanate group-containing silane coupling agent such as 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropylmethyldimethoxysilane, 3-isocyanatepropyltriethoxysilane, or 3-isocyanatepropylmethyldiethoxysilane is preferred. The coupling agent may be used alone or in combination of two or more.

[0067] The content of the coupling agent is preferably 0.05 to 5 parts by mass, more preferably 0.2 to 3 parts by mass, and even more preferably 0.5 to 2 parts by mass, relative to 100 parts by mass of the total of the moisture-curable resin (A) and the radically polymerizable compound (B). By keeping the content of the coupling agent within these ranges, adhesive strength can be improved without affecting the flexibility of the cured product.

[0068] (filler) The moisture-curable resin composition of the present invention may contain a filler. By containing a filler, the curable resin composition of the present invention has suitable thixotropy and is more likely to have good shape retention after application. As the filler, a particulate filler may be used. The filler is preferably an inorganic filler, such as silica, talc, titanium oxide, zinc oxide, or calcium carbonate. Among these, silica is preferred because it provides the light-and-moisture-curable resin composition with excellent ultraviolet transmittance. The filler may also be subjected to a hydrophobic surface treatment such as silylation, alkylation, or epoxidation. The fillers may be used alone or in combination of two or more. The content of the filler is preferably 1 part by mass or more and 25 parts by mass or less, more preferably 2 parts by mass or more and 15 parts by mass or less, relative to 100 parts by mass of the total amount of the moisture-curable resin (A) and the radically polymerizable compound (B).

[0069] The photo-curable resin composition of the present invention may contain, in addition to the components described above, other additives such as wax particles, ionic liquids, colorants, foamed particles, expanded particles, and reactive diluents. The photo-curable resin composition may be diluted with a solvent as needed. When the photo-curable resin composition is diluted with a solvent, the amount (parts by mass, %) of the photo-curable resin composition is based on the solid content, i.e., the parts by mass and % by mass excluding the solvent.

[0070] Examples of methods for producing the photo-curable resin composition of the present invention include a method of using a mixer to mix the moisture-curable resin (A), the radically polymerizable compound (B), the photopolymerization initiator (C), and other additives, such as a moisture-cure-accelerating catalyst, a filler, and a coupling agent, which are added as needed. Examples of mixers include a homodisper, a homomixer, a universal mixer, a planetary mixer (planetary stirring device), a kneader, and a three-roll mill.

[0071] <Cured body> The photo- and moisture-curable resin composition of the present invention is cured and used as a cured product. The cured product of the present invention is a cured product of a photo-moisture-curable resin composition containing a moisture-curable resin (A), a radically polymerizable compound (B), and a photopolymerization initiator (C), and has a swelling ratio (oleic acid swelling ratio) of 100% or more and 160% or less after immersion in oleic acid at 65°C and 90% RH for 72 hours, and a storage modulus of 1 MPa or more at 25% elongation. By virtue of the above-described configuration, the cured product of the present invention has excellent adhesive strength to adherends and maintains a high level of adhesive strength even after prolonged contact with sebum, sweat, chemicals, etc., and can be suitably used, for example, as an adhesive for portable electronic devices such as smartphones and wearable devices.

[0072] The oleic acid swelling ratio of the cured product is preferably 140% or less, more preferably 130% or less, and even more preferably 117% or less. The storage modulus of the cured product at 25% elongation is preferably 1.5 MPa or more, more preferably 2.0 MPa or more, and is not particularly limited, but is preferably 15 MPa or less, more preferably 10 MPa or less. The oleic acid swelling ratio and storage modulus at 25% elongation of the cured product can be determined by measuring these values ​​for the cured product using a method similar to that described in the Examples below.

[0073] The curable resin composition of the present invention can be applied to one of the adherends and then superimposed on the other adherend via the applied curable resin composition, for example, by curing the composition while the adherends are interposed between the adherends.

[0074] Furthermore, the photo-moisture-curable resin composition of the present invention may be photo-cured by light irradiation to, for example, a B-stage state (semi-cured state), and then further cured by moisture to fully cure. Here, when the photo-moisture-curable resin composition is placed between adherends and the adherends are bonded together, it is applied to one of the adherends and then photo-cured by light irradiation to, for example, a B-stage state. The other adherend is then placed on top of the photo-cured photo-moisture-curable resin composition, and the adherends are temporarily bonded together with an appropriate adhesive strength (initial adhesive strength). The photo-moisture-curable resin composition in the B-stage state is then fully cured by curing the moisture-curable resin (A) with moisture, and the adherends stacked together via the photo-moisture-curable resin composition are bonded together with sufficient adhesive strength (final adhesive strength).

[0075] The photo- and moisture-curable resin composition may be applied to the adherend using, for example, a dispenser, but is not particularly limited thereto. The light irradiated during photo-curing is not particularly limited as long as it is light that cures the radical polymerizable compound (B), but ultraviolet light is preferred. When the photo- and moisture-curable resin composition is fully cured by moisture, it may be left in the atmosphere for a predetermined time.

[0076] The photo-moisture-curable resin composition of the present invention is used, for example, as an adhesive for electronic devices, and is preferably used as an adhesive for portable electronic devices. Therefore, the adherend is not particularly limited, but is preferably various electronic components that constitute electronic devices. The material of the adherend may be any of metal, glass, plastic, etc. Furthermore, the shape of the adherend is not particularly limited, and examples thereof include a film, sheet, plate, panel, tray, rod (rod), box, and housing. Examples of portable electronic devices include, but are not limited to, mobile phones such as smartphones, digital cameras, wearable devices, portable game devices, tablet computers, notebook computers, and action cameras, with smartphones and wearable devices being preferred.

[0077] Electronic components generally have a substrate, and therefore, electronic components using the photo-moisture-curable resin composition of the present invention may have a cured product of the photo-moisture-curable resin composition and a substrate. Various electronic circuits are generally provided on the substrate. Similarly, electronic devices such as portable electronic devices using the photo-moisture-curable resin composition of the present invention may also have a cured product of the curable resin composition and a substrate.

[0078] In electronic components, for example, substrates may be used as adherends and bonded to each other via the photo-moisture-curable resin composition of the present invention, or a substrate may be bonded to other components of an electronic device (e.g., a housing) via the photo-moisture-curable resin composition of the present invention. For example, the light-curable resin composition of the present invention may be used to bond substrates together to obtain an assembled component inside an electronic device, etc. The assembled component thus obtained comprises a first substrate, a second substrate, and the cured product of the present invention, and at least a portion of the first substrate is bonded to at least a portion of the second substrate via the cured product. [Example]

[0079] The present invention will be explained in more detail by way of examples, but the present invention is not limited to these examples in any way.

[0080] In the present examples, various physical properties were measured as follows. (Oleic acid swelling rate) The photo-curable resin composition was poured into a Teflon mold measuring 10 mm in width, 50 mm in length, and 0.5 mm in thickness, and cured to obtain a cured film. The curable resin composition was cured using a UV-LED (wavelength 365 nm) with ultraviolet light at 1000 mJ / cm. 2 The coating was then exposed to light for light curing, and then allowed to stand at 25°C and 50% RH for 24 hours for moisture curing. 200 g of oleic acid (reagent, Fujifilm Wako Pure Chemical Industries, Ltd.) was placed in a glass container, and the cured film was immersed in the oleic acid in the container for 72 hours in an atmosphere of 65°C and 90% RH. The area of ​​the immersed cured film was then measured within 3 hours, and the ratio (%) of the area of ​​the cured film after immersion to the area of ​​the cured film before immersion was calculated and used as the oleic acid swelling ratio.

[0081] (Storage modulus at 25% elongation) The photo-curable resin composition was poured into a Teflon mold measuring 3 mm in width, 30 mm in length, and 1 mm in thickness, and cured to obtain a cured sample. The photo-curable resin composition was cured using a UV-LED (wavelength 365 nm) at 1000 mJ / cm. 2 The coating was then exposed to light for light curing, and then allowed to stand at 25°C and 50% RH for 24 hours for moisture curing. The cured sample was stretched to 100% elongation using a tensile tester (Autograph AG-X, manufactured by Shimadzu Corporation), and the modulus of elasticity at 25% elongation was calculated from the resulting tensile curve, which was taken as the storage modulus at 25% elongation. The measurement conditions were 25°C and a stretching speed of 5 mm / sec.

[0082] (Adhesive strength) As shown in Figures 1(a) and 1(b), a light- and moisture-curable resin composition 10 was applied to a polycarbonate plate 11 using a dispenser to a width of 1 mm ± 0.1 mm, a length of 25 ± 0.5 mm, and a thickness of 0.8 ± 0.4 mm. Within 1 minute after application, ultraviolet light of 1000 mJ / cm was applied using a UV-LED (wavelength 365 nm). 2 The curable resin composition 10 was photocured by irradiating the resin with light. Then, a glass plate 12 was placed on a polycarbonate plate 11 with the photo-moisture-curable resin composition 10 interposed therebetween, and a 100 g weight was placed on top of the glass plate 12 for 10 seconds, thereby applying a load of 0.04 MPa to the photocured product for 10 seconds. The 100 g weight was then removed, and the product was allowed to stand at 25°C and 50% RH for 24 hours to be moisture-cured, yielding an adhesion test sample 13. Six adhesion test samples 13 were prepared for each example and comparative example.

[0083] Three of the obtained adhesion test samples were left for a further 72 hours at 25°C and 50% RH, and then pulled in the shear direction S at a rate of 12 mm / sec. The strength at which the polycarbonate plate 11 and the glass plate 12 peeled off was measured, and the average value of the three samples was used as the adhesive strength before immersion in oleic acid (final adhesive strength). In addition, 200 g of oleic acid (reagent, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was placed in a container, and the adhesion test sample was immersed in the oleic acid in the container for 72 hours in an atmosphere of 65°C and 90% RH. Three adhesion test samples were similarly immersed in oleic acid. After immersion, the adhesion test sample was pulled in the shear direction S at a rate of 12 mm / sec within 3 hours, and the strength at which the polycarbonate plate 11 and the glass plate 12 peeled off was measured. The average value of the three measurements was taken as the adhesive strength after immersion in oleic acid (final adhesive strength). Then, the ratio (%) of the adhesive strength after immersion in oleic acid to the adhesive strength before immersion in oleic acid was calculated and defined as the adhesive strength maintenance rate.

[0084] The light- and moisture-curable resin compositions of the examples and comparative examples were evaluated as follows. [Oil resistance (adhesion strength after contact with oil)] The oil resistance was evaluated according to the following criteria based on the adhesive strength retention rate measured in each example and comparative example. AA: Adhesion strength retention rate was 50% or more. A: The adhesive strength retention rate was 30% or more and less than 50%. B: The adhesive strength retention rate was 10% or more and less than 30%. C: Adhesion strength retention rate was more than 0% and less than 10%. D: While the adhesion test sample was immersed in oleic acid, peeling occurred between the polycarbonate plate and the glass plate, and the adhesive strength retention rate was 0%.

[0085] [Adhesive strength] The adhesive strength was evaluated according to the following criteria based on the adhesive strength (final adhesive strength) measured in each example and comparative example before immersion in oleic acid. A: Adhesion strength before immersion in oleic acid is 150N / 25mm 2 That was all. B: Adhesion strength before immersion in oleic acid is 70N / 25mm 2 More than 150N / 25mm 2 It was less than. C: Adhesion strength before immersion in oleic acid is 70N / 25mm 2 It was less than.

[0086] [Room temperature application] The photo-moisture-curable resin composition of each example and comparative example was applied to a polycarbonate plate at room temperature (25°C) using a dispenser (nozzle inner diameter 0.61 mm, discharge pressure 0.35 MPa) to a width of 1 mm ± 0.2 mm and a length of 25 mm. If application was successful, the composition was evaluated as "A", and if application was not successful, the composition was evaluated as "B".

[0087] [Shape retention] The light-curable resin composition applied in the room temperature application evaluation was irradiated with ultraviolet light at 1000 mJ / cm using an LED lamp. 2 The film was irradiated and photocured, and the line width (t0) and height (t1) were measured after photocuring. The aspect ratio, expressed as t1 / t0 x 100 (%), was used to evaluate the film according to the following criteria. A: The aspect ratio is 50% or more. B: The aspect ratio is 30% or more and less than 50%. C: The aspect ratio is less than 30%.

[0088] The moisture-curable urethane resins used in the examples and comparative examples were prepared according to the following synthesis examples. [Synthesis Example 1] 100 parts by mass of a polycarbonate diol (a compound represented by formula (1), where 90 mol% of R is a 3-methylpentylene group and 10 mol% is a hexamethylene group; manufactured by Kuraray Co., Ltd., trade name "Kuraraypolyol C-1090") as a polyol compound and 0.01 parts by mass of dibutyltin dilaurate were placed in a 500 mL separable flask. The contents of the flask were stirred at 100°C for 30 minutes under vacuum (20 mmHg or less). The pressure was then returned to normal pressure, and 50 parts by mass of diphenylmethane diisocyanate (manufactured by Nisso Shoji Co., Ltd., trade name "Pure MDI") as a polyisocyanate compound was added. The mixture was stirred at 80°C for 3 hours to react, yielding a moisture-curable urethane resin (PC skeleton, aromatic-terminated urethane) with a polycarbonate (PC) skeleton and aromatic isocyanate groups at both ends. The weight-average molecular weight of the resulting moisture-curable urethane resin was 6,000.

[0089] [Synthesis Example 2] 100 parts by weight of a polyester polyol (polyester polyol obtained primarily from adipic acid, 1,6-hexanediol, and isophthalic acid, aromatic ring concentration 15% by weight, weight-average molecular weight 1000) and 0.01 parts by weight of dibutyltin dilaurate were placed in a 500 mL separable flask. The mixture was stirred and mixed under vacuum (20 mmHg or less) at 100°C for 30 minutes. The pressure was then returned to normal, and 52.5 parts by weight of diphenylmethane diisocyanate (manufactured by Nisso Shoji Co., Ltd., trade name "Pure MDI") was added as a polyisocyanate compound. The mixture was stirred and reacted at 80°C for 3 hours to obtain a moisture-curable urethane resin (polyester skeleton aromatic-terminated urethane) containing a polyester skeleton and terminated at both ends by aromatic isocyanate groups. The resulting moisture-curable urethane resin had a weight-average molecular weight of 1500.

[0090] [Synthesis Example 3] 100 parts by weight of polytetramethylene ether glycol (manufactured by Mitsubishi Chemical Corporation, trade name "PTMG-2000") as a polyol compound and 0.01 parts by weight of dibutyltin dilaurate were placed in a 500 mL separable flask and mixed under vacuum (20 mmHg or less) at 100 °C for 30 minutes with stirring. The pressure was then returned to normal, and 26.5 parts by weight of diphenylmethane diisocyanate (manufactured by Nisso Shoji Co., Ltd., trade name "Pure MDI") as a polyisocyanate compound was added. The mixture was stirred at 80 °C for 3 hours to react, resulting in a moisture-curing urethane resin (ether skeleton aromatic terminal urethane) having a polyether skeleton and aromatic isocyanate groups at both ends. The weight-average molecular weight of the resulting moisture-curing urethane resin was 2700.

[0091] The components other than the moisture-curable urethane resin used in each of the Examples and Comparative Examples were as follows: (Radical polymerizable compound) Imide ring-containing acrylate: Toagosei Co., Ltd., product name "M-140", N-acryloyloxyethyl hexahydrophthalimide, monofunctional Urethane acrylate (1): Rahn AG, trade name "GENOMER 1122", monofunctional aliphatic urethane acrylate Aromatic ring-containing acrylate: Kyoeisha Chemical Co., Ltd., product name "Light Acrylate PO-A", phenoxyethyl acrylate, monofunctional Urethane acrylate (2): Daicel-Allnex Corporation, trade name "EBECRYL8411", multifunctional, weight average molecular weight 12000, diluted with 20% by mass of isobornyl acrylate (IBOA), urethane acrylate content 80% by mass Lauryl acrylate: Kyoeisha Chemical Co., Ltd., product name "Light Acrylate LA", monofunctional Photopolymerization initiator: 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, manufactured by BASF, trade name "IRGACURE 369" Coupling agent: 3-isocyanatepropyltriethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBE-9007N" Filler: Trimethylsilylated silica, manufactured by Nippon Aerosil Co., Ltd., product name "R812", primary particle size 7 nm

[0092] [Examples 1 to 8, Comparative Examples 1 to 3] According to the compounding ratios shown in Table 1, each material was stirred at a temperature of 50°C using a planetary stirrer (Thinky Corporation, "Awatori Rentaro"), and then uniformly mixed at a temperature of 50°C using a ceramic three-roll mill to obtain the light-moisture-curable resin compositions of Examples 1 to 8 and Comparative Examples 1 to 3.

[0093] [Table 1]

[0094] As shown in Table 1, the light- and moisture-curable resin compositions of each example had a low oleic acid swelling ratio and a storage modulus of 1 MPa or more at 25% elongation, which improved the final adhesive strength after light and moisture curing and allowed the adhesive strength to be well maintained even after swelling with oleic acid. Therefore, they can be suitably used as adhesives for portable electronic devices that often come into contact with sebum, sweat, chemicals, etc. In contrast, the light- and moisture-curable resin compositions of each comparative example had an oleic acid swelling ratio of more than 160% or a storage modulus at 25% elongation of less than 1 MPa, resulting in low final adhesive strength after light and moisture curing or inability to maintain good adhesive strength after swelling with oleic acid. Therefore, they are not suitable for use in portable electronic devices that frequently come into contact with sebum, sweat, chemicals, etc.

Claims

1. A photo-curable moisture-curable resin composition containing a moisture-curable urethane resin (A), a radical polymerizable compound (B), and a photopolymerization initiator (C), the moisture-curable urethane resin (A) contains at least one selected from the group consisting of moisture-curable urethane resins having a polycarbonate skeleton and moisture-curable urethane resins having a polyester skeleton, and has an aromatic isocyanate group; the radical polymerizable compound (B) contains at least one selected from the group consisting of a radical polymerizable compound having an aromatic ring and a radical polymerizable compound having an imide ring, the content of the moisture-curable urethane resin (A) is 15% by mass or more and 85% by mass or less, and the content of the radical polymerizable compound (B) is 14% by mass or more and 84% by mass or less, based on the total amount of the photo-moisture-curable resin composition; A photo-moisture-curable resin composition, wherein the swelling ratio after immersing a cured product of the photo-moisture-curable resin composition in oleic acid at 65°C and 90% RH for 72 hours is 100% or more and 160% or less, and the storage modulus of the cured product at 25% elongation is 1 MPa or more.

2. The photo-curable moisture-curable resin composition according to claim 1, wherein the moisture-curable urethane resin (A) comprises a moisture-curable urethane resin having a polycarbonate skeleton and an aromatic isocyanate group.

3. The photo-curable moisture-curable resin composition according to claim 1 or 2, wherein the radical polymerizable compound (B) contains a radical polymerizable compound having an imide ring.

4. An adhesive for electronic components, comprising the light-curable moisture-curable resin composition according to any one of claims 1 to 3.

5. An adhesive for portable electronic devices, comprising the light-curable moisture-curable resin composition according to any one of claims 1 to 3.

6. A cured product of a photo-curable moisture-curable resin composition containing a moisture-curable urethane resin (A), a radical polymerizable compound (B), and a photopolymerization initiator, the moisture-curable urethane resin (A) contains at least one selected from the group consisting of moisture-curable urethane resins having a polycarbonate skeleton and moisture-curable urethane resins having a polyester skeleton, and has an aromatic isocyanate group; the radical polymerizable compound (B) contains at least one selected from the group consisting of a radical polymerizable compound having an aromatic ring and a radical polymerizable compound having an imide ring, the content of the moisture-curable urethane resin (A) is 15% by mass or more and 85% by mass or less, and the content of the radical polymerizable compound (B) is 14% by mass or more and 84% by mass or less, based on the total amount of the photo-moisture-curable resin composition; A cured product having a swelling rate of 100% or more and 160% or less after immersion in oleic acid at 65°C and 90% RH for 72 hours, and a storage modulus of 1 MPa or more at 25% elongation.

7. An electronic component comprising the cured product according to claim 6 and a substrate.

8. A portable electronic device comprising the cured product according to claim 6 and a substrate.

Citation Information

Patent Citations

  • Polyurethane composition

    JP2019214646A

  • Polycarbonate diol and aqueous polyurethane dispersion using the same

    JP2020007400A

  • Polycarbonate diol, method for producing the same and polyurethane using the same

    JP2020029569A

  • Coating composition

    JP2020055900A

  • Light / moisture-curable resin composition, adhesive for electronic component, and adhesive for display device

    WO2015056717A1